Genetic strain differences in platelet aggregation of laboratory mice - Sudo, Toshiki; Ito, Hideki; Kimura, Yukio (Thrombosis and Haemostasis, 2006)
To investigate the physiological role of novel genes and proteins in platelet activation, various knockout mice have been produced. A number of standard inbred mouse strains each possessing genetically unique characters such as high tumor generation, hyperglycemia or hyperlipidemia, have been bred. In breeding knockout mice for investigation of specific physiological functions, appropriate selection of parental or backcross strains is necessary. Thus, examination of strain-specific platelet characteristics is important. In the present study, platelet aggregation responses of 13 laboratory mouse strains, 129/Sv, A, AKR, BALB/c, C3H/He, C57BL/6J, CBA, DBA/1, DBA/2, ddY, FVB, ICR, and NZW, and the diabetic strain C57BL/KsJ db/db, were compared. Marked strain differences were observed inADP- and collagen-induced platelet aggregation. The highest responses with both were seen in AKR/J and NZW/N, whereas the lowest were seen in DBA/2 and DBA/1.There was a 5-fold difference in the platelet aggregation threshold index (PATI) for ADP-induced PRP aggregation between AKR/J (0.6 µM) and DBA/2 (3.0 µM). With whole blood aggregation, the highest response was seen in AKR, whereas the lowest was seen in DBA/2 and DBA/1. The present study demonstrated that there is considerable strain difference in platelet aggregation among laboratory mice, which should be taken into account in backcrossing knockout strains.
Keywords: Platelet aggregation; mouse; strain difference